Transitional Care Interventions as Implemented By Faith Community Nurses - (:unkn) unknown (My University, 2016)
Hospitals are seeking innovative and efficient methods of decreasing avoidable readmissions. Despite the volume of nursing literature exploring the use of advanced practices nurses in providing transitional care, only one study mentions the use of a faith community nurse. The faith community nurse operates in the community and has the skills to provide transitional care. The purpose of this study was to describe transitional care as implemented by faith community nurses using a standardized nursing language: the Nursing Intervention Classification (NIC). A mixed method descriptive design was selected to facilitate a thorough exploration of the interventions implemented by faith community nurses. The findings suggested that the majority of interventions are in the coping assistance, communication enhancement, and patient education Classes of the Behavioral Domain. The most frequently selected nursing interventions in NIC (n=26) were found and validated by the faith community nurse focus group. Results were compared to evidenced-based priority transitional care interventions described in research. In addition, results were compared to previous faith community nursing research describing the practice. Results were also described using the Faith Community Nursing conceptual framework. The results may provide the underpinnings for further testing of transitional care interventions.
Keywords: Faith Community Nursing; Nursing Intervention Classification; Transitional Care; Wholistic Health Care